1990
DOI: 10.4098/at.arch.90-25
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in hematological values and heart weight in two small mammals, a mouse: Apodemus sylvaticus, and a vole: Pitymys duodecimcostatus

Abstract: López-Luna P. 1990. Seasonal variations in hematological values and heart weight in two small mammals, a mouse Apodemus sylvaticus, and a vole: Pitymys duodecimcostatus. .Hematological values and relative heart weight were analyzed in two rodents: the mouse, Apodemus sylvaticus (Linnaeus, 1758), and the vole, Pitymys duodecimcostatus (de Sélys-Longchamps, 1839). The body weight of the two species was similar, 18.60 + 0.61 g for the mouse, versus 20.14 + 0.42 g for the vole. The specimens were captured in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Under laboratory conditions, Teijon et al [49] observed a small increase in rat lysozyme activity compared to the control group after oral administration of lead. Analogous to the findings of previous studies on small mammals [50], we observed no sexual differences or age‐related effects for the hematological characteristics of the wood mice.…”
Section: Discussionsupporting
confidence: 90%
“…Under laboratory conditions, Teijon et al [49] observed a small increase in rat lysozyme activity compared to the control group after oral administration of lead. Analogous to the findings of previous studies on small mammals [50], we observed no sexual differences or age‐related effects for the hematological characteristics of the wood mice.…”
Section: Discussionsupporting
confidence: 90%
“…Discrepancies between studies in the type and/or number of parameters significantly related to pollution may be partly explained by differences in puncture sites, which may impact blood parameter estimations (Bonnet et al 2016), and the season of sampling. Seasonal variations in haematology have indeed been reported for fish species (de Pedro et al, 2005), birds (Ots et al, 1998) or small mammals (Perez-Suarez et al, 1990;Beldomenico et al, 2008), and may be attributed to changes in diet (Thompson et al, 1997), physiological needs for preparing (or during) breeding season (Rai and Haldar, 2003), or higher metabolic rate in response to their acclimatization to low temperature during winter (Pérez-Suarez et al, 1990). Further, reproductive status (Ferrer, 1990;Nunes et al, 2001), diurnal time (Ots et al, 1998), periods of population growth or decline (Tarakhtii et al, 2007a;2007b), or infection status (Maceda-Veiga et al, 2015) modify haematological parameters as well.…”
Section: Erythrocyte Indicatorsmentioning
confidence: 99%
“…Further, reproductive status (Ferrer, 1990;Nunes et al, 2001), diurnal time (Ots et al, 1998), periods of population growth or decline (Tarakhtii et al, 2007a;2007b), or infection status (Maceda-Veiga et al, 2015) modify haematological parameters as well. For instance, during pregnancy of wood mice, Perez-Suarez et al (1990) found sexual differences in haematocrit, haemoglobin or total RBC number. In the present study, differences between males and females as well as between juveniles and adults were detected in both species (Fig.…”
Section: Erythrocyte Indicatorsmentioning
confidence: 99%
“…The hematological characters of wild animals are becoming increasingly important as diagnostic tools for physiological and taxonomic studies of small mammals. The responses of rodents to anthropogenic changes in habitats may indicate physiological stress due to diminished environmental quality (Pérez-Suárez et al 1990).…”
Section: Introductionmentioning
confidence: 99%